(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The theory of testing human physical fitness is one of the most fully developed in the field of sports theory. Of particular importance for the use of test results is the development of various standards. Standards are developed for a certain group of athletes and are valid only for it [1]. The most popular test or control exercise is the 30m run from the high start, a total of four speed ability assessment tests are offered – a 20m run from a high start, a 30m run from a high start, a 60m run from a high start and a 100m run from a high start. Not all sports mention normative results for women and men. Standards in professionally oriented sports, such as boxing, judo, football, hockey, karate, rugby and Nordic combined, are for men only. Such sports as boxing, judo and karate have the same control standards. In turn, in athletics, they are divided according to disciplines. The difference in results during testing is 0.5 seconds, as different systems for recording results are used – with a handheld stopwatch and an electronic result-recording machine. The highest requirements for High Performance Sport groups in the 20m race are set for men in gymnastics – 3.0seconds, and for women in weightlifting – 3.2seconds. The average score in sports where the speed test for the High-Performance Sport group is a 20-meter run from the spot is 3.5±0.19seconds for men and 3.6±0.19seconds for women. Coaches of sports schools choose to fix the results with a hand stopwatch. Aim of the study: Evaluation of speed tests and control exercises in sports practice in Latvia.